When did you see her last? ebook - Snicket, Lemony (All the Wrong Questions, 2013)
★  "Fans of A Series of Unfortunate Events will be in heaven."― Kirkus Reviews, starred review Before the Baudelaires became orphans, before he encountered A Series of Unfortunate Events, even before the invention of Netflix, Lemony Snicket was a boy discovering the mysteries of the world. This is his story. In the fading town of Stain’d-by-the-Sea, young apprentice Lemony Snicket has a new case to solve when he and his chaperone are hired to find a missing girl. Is the girl a runaway? Or was she kidnapped? Was she seen last at the grocery store? Or could she have stopped at the diner? Is it really any of your business? These are All The Wrong Questions. The mystery continues in Shouldn’t You Be in School?  and Why Is This Night Different from All Other Nights? , both available now.